Comparison of Medication Administration Errors (MAEs) and order returns between two wards in a tertiary government hospital with and without a modified Unit Dose Drug Distribution System (UDDDS) - Aloc, Angelica R.
Objectives: The study aimed to compare the frequency of medication administration errors (MAEs) and order returns between two wards of a tertiary government hospital with and without UDDDS.